Effects of a physical therapy home-based exercise program for Parkinson's disease - Viviane Vieira Santos; Marco Antonio Araújo; Osvaldo J. M Nascimento; Fernando Silva Guimarães; Marco Orsini; Marcos R. G. de Freitas
INTRODUCTION: Parkinson's disease (PD) is a neurological disorder that causes loss of functional abilities and independence. The aim of this study was to evaluate the effects of a physical therapist-supervised home-based exercise program in patients with PD using the UPDRS scale. MATERIALS AND METHODS: Thirty-three PD patients in the 1.5 to 3 Hoehn and Yahr stages participated in the trial. The patients and their relatives received a booklet with a 12-week home program, with a series of strengthening, stretching and flexibility exercises. The patients were trained by a physical therapist, and each session took 60 minutes, three times a week. RESULTS: We classified our patients in four groups: Group 1 - patients under 60 years of age and less than five years of PD; Group 2 - patients under 60 years of age and more than five years of PD; Group 3 - patients over 60 years of age and less than five years of the disease; and Group 4 - patients over 60 years of age and more than five years of PD. Significant improvement was found in group 1 in mentation, activities of daily living and motor function (p > 0.05). Group 3 presented statistically significant differences in motor function subscale (p > 0.05) and Group 4 showed no worsening in mentation subscale (p > 0.05). Group 2, however, presented no difference in all subscales (p < 0.05). CONCLUSION: Although not all patients improved their UPDRS scores, our data support the use of a home program as an alternative method of physical therapy treatment for PD patients.